Detection of potential drug-drug interactions among ovarian cancer patients in a tertiary care teaching hospital in South India- A retrospective approach - Kala Bahadur Rawal; Uday Venkat Mateti; Vijith Shetty; M.K. Unnikrishnan; C.S. Shastry (Elsevier, 2023)
Background: Potential drug-drug interactions (pDDIs) can alter therapeutic efficacy, involve adverse reactions, and generate novel responses not elicited when either agent is used alone. pDDIs can contribute to morbidity and mortality. Cancer patients are at high risk of pDDIs because of polypharmacy necessitated by chemotherapy, hormone therapy, and supportive care medications. Our study was designed to quantify the prevalence of pDDIs among ovarian cancer patients in a tertiary care teaching hospital in South India. Materials and methods: We retrospectively analysed data gathered over two years on ovarian cancer patients 18 years and above undergoing antineoplastic therapy (other than radiation and surgery). The patient's treatment charts were reviewed, and the drugs prescribed were analysed for the possible pDDIs using UpToDate software (Lexicomp® database). Results: A total of 354 pDDIs were detected among 92 patients included in the study, with (56.5%; n = 200) experiencing moderate severity. (52.3%; n = 158) pDDIs fell under pDDIs risk category D, and pDDIs reliability rating was 'fair' in (76.8%; n = 272). Most commonly observed pDDIs for neoplastic agents occurred between paclitaxel and carboplatin (16.4%; n = 58) and between ondansetron and domperidone under supportive therapy (20.9%; n = 74). Polypharmacy accounted for 100% of inpatient prescriptions and 50% of prescriptions at discharge. Conclusion: Ovarian cancer poses a significant risk of pDDIs and requires an interdisciplinary vigilance policy to prevent, minimize, and manage unwanted effects of pDDIs.